Smart Calculator 2.0 / Siti Noor Dina Ahmad ... [et al.] - Ahmad, Siti Noor Dina; Mohamed, Nadiah; Mahayadin, Mahfuzah; Mohd Ruslan, Siti Zaharah; Ismail, Norul Fadhilah; Sahrom, Nor Ashikin; Othman, Norlida; Yaacob, Nurul Aityqah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Smart Calculator 2.0 Program was organized by the School of Computing and Mathematic, UiTM Negeri Sembilan Campus Kuala Pilah on May 12, 2023. The program was led by Ms. Nadiah Mohamed as the program advisor aimed to assist students in using scientific calculators by providing a platform to prepare for final exams. A total of 73 students participated, including Pre-Science, STEM C, and Pre-Academy of Contemporary Islamic Studies students. The program was facilitated by six talented and dedicated students. The feedback from the participating students was very positive, and they suggested that the program should continue in the future. Figurel illustrates the poster for the Smart Calculator 2.0 program.